(untitled) (London, 1971)
Contents: Overall report by Hla Myint, The green revolution in Southeast Asia in the 1970s by Harry Walters and Joseph Willett, The manufacturing industry sector by Helen Hughes,...
Keywords: Đông Nam Á,Southeast Asia; Điều kiện kinh tế,Economic conditions